Malaycious: usable mobile food finding application - Lee, Pui Yen; Zaaba, Zarul Fitri (2016)
Food-finding application is an application that provides users with classified and suggestive information about the local food one particular country. Apparently, there are numbers of the food-finding applications in the Malaysia’s apps market such as Malaysia Food diary, Hungry go where, Food Spotting etc. However, lacks of classified and suggestive information are the main limitations of the current applications.In order to overcome the limitations of the existing applications, features such as augmented reality, photographic food diary, and smart budget are implemented in the proposed solution.A survey is conducted to understand end-users insights on their usage of food finding application in Malaysia.Based on the gathered evidence, Malaycious is introduced as a new food finding application that bridges the gap of known challenges.Augmented reality (AR) is implemented in the proposed system to enrich users camera feed with contextual information.Users can now benefits from the ability to the place computer generated graphics in the field of vision.Besides that, shooting food becomes one of the fastest growing hobbies for people nowadays. Therefore, the proposed application will include a new feature called Photographic Food Diary to store that pictures that users capture.Therefore, users can recall back the images and also the information of the images.In addition, Smart Budget is a feature that help users to filter the food according to the preferences that user entered.The detail discussion were provided in the relation to the development of Malaycious.Therefore, it can be suggested that Malaycious provide usable and user-friendly food-finding application.